Logiken der Sammlung - Dallinger, Petra-Maria (Literatur und Archiv, 2020)
The archive and its various forms as storage of cultural memory are the focus of the fourth volume of the literature and archive series. What does it mean when an archive is only dedicated to a holder, when there are estate units in libraries and depots of museum institutions or in administration archives? When looking at different collection facilities and their specific challenges, not only differences are revealed, but also parallels and interfaces of a heterogeneous archive landscape.